(untitled) (Proceedings of the International Conference on Public Health, 2025)
Studies on racial disparity of uterine fibroids (UFs) indicate that Black women are three times more at risk of being diagnosed than other racial groups. Yet most available trusted medical treatments for UFs and public health policy overlook this common illness as well as the needs of Black women. This study examines the perceptions, uses and benefits of herbal medicines used for the treatment of UFs amongst South African women. Online testimonies and reviews from clients were retrieved from the suppliers’ online pages (n=60) and social media platforms: Instagram (n=6) and TikTok (n=18). Data analysed through thematic analysis revealed seven themes. i.e. i): regulating the menstrual cycle, ii)’ relief from unpleasant menstrual symptoms’, iii) ’proof that the medicines are working -confirmed by a medical practitioner’, iv) ’proof that the medicines are working confirmed by medical practitioner’, v)’ reasons for using herbal medicines’, vi)’ time lapse before feeling the effects of the herbal medicines and vii)’ other female reproductive benefits’. Women appreciate the ability of herbal medicines to relieve menstrual pains, regulate the cycle, and improve overall sexual reproductive health. However, the research gaps in ascertaining herbal medicines’ efficacy still need to be addressed. Further studies are required to investigate the correlation between reduced symptomology, a placebo effect, the mechanism of action and the associated safety profile of herbal medicines.